TINGKAT KETERAMPILAN SHOOTING FUTSAL PADA PESERTA DIDIK EKSTRAKURIKULER SMP NEGERI 1 MARTAPURA - Nurramadhan, Raihan; Ramadhan Arifin; M. Mulhim (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
TThe field is short and mistakes are almost impossible in futsal because of the game's high speed and intensity. Using a sample population of SMP Negeri 1 Martapura extracurricular students, this research is a quantitative descriptive study employing a purposive sampling approach. According to the futsal shooting results of SMP Negeri 1 Martapura extracurricular students, the category of "very good" is 0% (0 people), "good" is 10% (2 people), "fair" is 20% (4 people) , "poor" is 70% (14 people), and "Very Poor" is 0% (0 people). Simple futsal shooting methods will not be optimal as the student's body is still standing straight, their eyes are not fixed on the ball, their foot does not make perfect contact with the ball behind their foot, and they have not had enough shooting experience. 70% of futsal shooters fall into the fewer than 14 categories, which include 14 players. The findings suggest that the futsal players at SMP Negeri 1 Martapura who participate in extracurricular activities have poor shooting skills.